Biology of Crocidura sibirica Dukelsky, 1930 in the southern West Siberia ... - Luchnikova, Ekaterina M.; Ilyashenko, Vadim B.; Kovalevskiy, Alexander V.; Zubko, Kirill S.; Vdovina, Evgeniya D.; Teplova, Natalya S. (Altai State University, 2023)
Our paper reflects the data of a comprehensive study of the main biological characteristics of the Siberian shrew Crocidura sibirica Dukelsky, 1930. 921 specimens were examined for the period 1978–2020. It has been found that the Siberian shrew is attracted to habitats that have been significantly disturbed by human activity (logging sites, hayfields, reclaimed coal dumps, burned areas), but avoids completely degraded areas and urban ecosystems. It reaches its maximum abundance in the low-mountain belt of the Kuznetsk Alatau in hay meadows. The population of the Siberian shrew is subject to cyclic fluctuations with a frequency of 3–4 years. Seasonal activity peaks in mid-August and September, with breeding in the second half of summer and early fall. Among the one-year-old animals, the predominance of males is observed. The diurnal activity of the Siberian shrew is polyphasic, mainly nocturnal. Peaks of highest activity were observed at 23–24 hours and 6–9 hours. In terms of running speed, digging ability, ...